The chocolate pirate plot - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2010)
Ever since Young Blackbeard became a hit movie, everyone has caught pirate fever, including the residents of Warner Pier. TenHuis Chocolate is selling out of chocolate treasure chests, pirate hats and ships. When Lee McKinney Woodyard and her husband take their boat out on Lake Michigan, they're stunned when a mischievous band of pirates hops on board. Lee's is the first boat boarded that summer, and the town couldn't be more amused by the mysterious buccaneers. But when a body washes up on shore, the pirates' antics stop being so entertaining...